First-phase ejection fraction is associated with myocardial fibrosis in the pressure overloaded heart - He, Shukun; Jiang, Jingrong; Zhang, Yanting; Liu, Tianshu; Deng, Wenhui; Xie, Yuji; Li, Wenqu; Tan, Yuting; Fang, Lingyun; Zhang, Jing; He, Lin; Jin, Qiaofeng; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundFirst-phase ejection fraction (EF1) has been recently demonstrated to sensitively detect early cardiac systolic dysfunction. However, the value of EF1 in predicting myocardial fibrosis (MF) has not been investigated. This study aimed to explore the relationship between EF1 and MF in the pressure overloaded heart.MethodsThe pressure overloaded heart was induced by minimally invasive transverse aortic constriction (MTAC) in rats. Rats in the sham and MTAC groups were equally divided into different time points for examination, respectively. Echocardiography was conducted to validate the success of MTAC model and measure cardiac systolic function parameters. Subsequently, rat hearts underwent Masson's staining to measure the degree of MF.ResultsCompared with sham group rats, MTAC group rats exhibited a significantly progressive impairment in EF1 starting from the 2nd week over observational period (P < 0.01), while GLS, GCS, GRS and EF showed no significant difference until the 3rd week and 4th week respectively. MF strongly correlated with EF1 (r = −0.78, P < 0.001), modestly with GLS, GCS and GRS (r = −0.65 to −0.51, P < 0.001), and weakly with EF (r = −0.42, P < 0.05). Receiver operating characteristic curve indicated that EF1 exhibits excellent performance in the detection of moderate and severe MF (area under the curve = 0.87, P < 0.001).ConclusionsEF1 represents a highly sensitive and non-invasive marker for the early detection of cardiac systolic dysfunction and emerges as a promising indicator for the identification of MF in the early stage of pressure overloaded heart.